2021
DOI: 10.3389/fspor.2021.696264
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Motivation, Socialization, Wellness and Mental Health in Youth Long-Distance Runners During COVID-19 Social Distancing Restrictions

Abstract: Purpose: The COVID-19 pandemic impacted the sporting and exercise activities of millions of youth. Running is an activity that could be maintained while social distancing restrictions were implemented during the pandemic. However, a recent study has indicated that youth runners reported lower running distance, frequency, and intensity during COVID-19. The reason for this reduction and the impact on overall well-being is unknown. Therefore, the purpose of this study was to determine if the social distancing res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 42 publications
(79 reference statements)
2
6
0
Order By: Relevance
“…Our study confirms that among runners who had had COVID-19, affiliation was not a significant factor, which was also reflected in the findings by DeJong and colleagues [19]. The health benefits of running, on the other hand, remained a strong motivator, and in fact strengthened after COVID-19 developed, as confirmed by our study in addition to other studies [33].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study confirms that among runners who had had COVID-19, affiliation was not a significant factor, which was also reflected in the findings by DeJong and colleagues [19]. The health benefits of running, on the other hand, remained a strong motivator, and in fact strengthened after COVID-19 developed, as confirmed by our study in addition to other studies [33].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, it is an activity that has been able to be sustained while social distancing restrictions were being introduced during the pandemic. However, a study conducted on a group of adolescent runners aged 9-19 years found that the social distance constraints of COVID-19, including restrictions on competition or team interaction, resulted in a significant decrease in motivation and enjoyment of running [33]. Such results are confirmed by many other studies, showing that the psychological effects of the COVID-19 pandemic are apparent in various social groups, and the lack of motivation behind engaging in any activity, apart from symptoms of anxiety, depression or post-traumatic stress disorder, is one of the most common causes of its occurrence [34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…The authors declare no conflict of interest and do not have any financial disclosures. Nutritional balance (81,88) Ensure adequate nutritional intake to combat infection; Encourage personal tracking of dietary intake of macro and micronutrients especially vitamins A, B6, B12, C, D, E, and folate) and other elements (i.e., zinc, iron, selenium, magnesium, and copper), which can modulate viral infection course; focus on healthy food patterns and maintenance of normal meals and time of consumption. e.g., Minimize deviations from healthy eating patterns (avoid consumption of foods with high saturated fat, high sugar content) and obtain high intake of fiber, whole grains, unsaturated fats, and antioxidants using phone tracking apps or food logs; avoid eating large meals late at night.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cancellation of public events, such as running races, contributed to lack of motivation to run, worry about changes in training on different surfaces, and loneliness without supportive runners to participate with (11). Even young athletes experienced these mood changes, reduction in well-being, and loss of motivation, as observed in long-distance runners (81).…”
Section: Mental Health Impact Of Covid On Athletesmentioning
confidence: 99%
“…Further, many countries relied on telemedicine and remote pharmaceutical services for healthcare delivery [ 9 ]. Consequently, professional socialisation was significantly impacted, for there were restrictive measures on visiting offices [ 10 ]. Given that the probability of contracting the COVID-19 infection is remarkably higher in the healthcare workplaces than in other places, the pandemic has a larger influence on professional socialisation in healthcare than in other professions.…”
Section: Professional Socialisation In Times Of Pandemicsmentioning
confidence: 99%